Differences in the Subjective Well-Being of Undergraduate Students Based on Birth Order - Mariana Adira Bani Bangu; Dian Lestari Anakaka; Indra Yohanes Kiling (Universitas Nusa Cendana, 2021)
Abstract: Subjective well-being is an important thing in one's life. Various ways are done by someone to feel welfare in his life. The position of the child in the order of birth is a condition that is determined at the time of conception, has a fundamental influence on its subsequent development. This is because parents generally have specific attitudes, treatments, and roles for their oldest child, middle child, and youngest child. The purpose of this study was to determine whether there are differences in the subjective welfare of Undana students based on birth order. The sampling technique used the Cochran formula with a standard error of 5%. So that the researchers managed to collect data as many as 433 students aged 18-24 years and have two or more siblings. The analysis in this study used an ANOVA significance value of 0.048 <0.05, so that H0 was rejected. If H0 is rejected, there is a significant difference in subjective welfare based on the birth order of students at the University of Nusa CendanaKupang.